Caladium Cultivars ‘Cosmic Delight’, ‘Fiesta’ and ‘Hearts Desire’ - Zhanao Deng (EDIS, 2017)
Caladiums are commonly grown in containers, hanging baskets or planted directly in the landscape as accent and border plants. Florida growers supply the majority of the caladium tubers used throughout the United States and around the world. The University of Florida’s Institute of Food and Agricultural Sciences (UF/IFAS) has maintained a caladium breeding program at the Gulf Coast Research and Education Center (GCREC). This program released three new caladium cultivars, ‘Cosmic Delight’, ‘Fiesta’, and ‘Hearts Desire’, in 2015. This publication describes the origin and plant characteristics of these new cultivars, their tuber yield potential in production trials, and plant performances in container and landscape trials. These new cultivar introductions will be valuable to the Florida caladium tuber-production industry, the greenhouse/nursery industries, and commercial landscape maintenance companies.